The Traveler and His Diary: Couto de Magalhães and Roger Casement - Machado, Maria Helena Toledo Pereira (ABEI Journal, 2011)
The aim of this article is to reflect upon the process of constructionof the travel narrative as a counterpoint to the traveler’s experience. Itfocuses the travels of two public figures, General Couto de Magalhães andthe Irish nationalist Roger Casement. Their intimate diaries written duringtheir travels are analysed from a critical perspective that considers thetensions between the actual travel experience and its subsequent publishedaccount. The issues addressed along this text are genre, sexuality, narrativeconstruction and travel literature.